Facial Cosmetics Have Little Effect on Attractiveness Judgments Compared with Identity. (January 2015) - Jones, Alex L; Kramer, Robin S S
The vast majority of women in modern societies use facial cosmetics, which modify facial cues to attractiveness. However, the size of this increase remains unclear—how much more attractive are individuals after an application of cosmetics? Here, we utilised a 'new statistics' approach, calculating the effect size of cosmetics on attractiveness using a within-subjects design, and compared this with the effect size due to identity—that is, the inherent differences in attractiveness between people. Women were photographed with and without cosmetics, and these images were rated for attractiveness by a second group of participants. The proportion of variance in attractiveness explained by identity was much greater than the variance within models due to cosmetics. This result was unchanged after statistically controlling for the perceived amount of cosmetics that each model used. Although cosmetics increase attractiveness, the effect is small, and the benefits of cosmetics may be inflated in everyday thinking.